Rare genetic variants prioritize molecular pathways for semaphorin interactions in Alzheimer's disease patients. Issue 1 (1st January 2021) - Balabanski, Lubomir; Serbezov, Dimitar; Atanasoska, Maya; Karachanak-Yankova, Sena; Hadjidekova, Savina; Nikolova, Dragomira; Boyanova, Olga; Staneva, Rada; Vazharova, Radoslava; Mihailova, Marta; Damyanova, Vera; Nesheva, Desislava; et al.
Abstract: Contemporary genetic methods have not yet solved the 'missing heritability' problem of complex diseases such as Alzheimer's disease (AD). The impact of rare or less common variation on human complex diseases and traits remains to date barely investigated. In this study rare population variants detected using whole-exome sequencing were employed to examine how molecular pathways are prioritized in four groups: Alzheimer's disease (AD) patients, Frontotemporal dementia (FTD) patients, young and healthy individuals and centenarians. The set of prioritized genes in AD patients associated with Semaphorin interactions pathways, contrasting with the results of the other groups. We identified rare pathogenic, likely pathogenic and variants of unknown significance in these prioritized genes in AD patients. The results of this study offer evidence that semaphorin pathways play a role in AD genetic etiology.